Patagonia's path to carbon neutrality by 2025 - Kammen, Daniel M., 1962-; Hendricks, Paul; Pendleton-Knoll, Seren; Stanley, Vincent; Strand, Robert (London : The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business, 2018)
This case study describes Patagonia's goal to become carbon neutral by 2025 in an absolute sense--that is to reduce emissions to zero while still growing the company. Patagonia also wants to achieve absolute carbon neutrality in such a way that other interested companies can replicate. The case explores aspects of this goal through the eyes of a number of Patagonia employees who work on different teams within the apparel and gear business. (As a whole, Patagonia includes both the long-established apparel and gear operations and the more-recently formed food line Provisions. However, the company's goal, as described in the case, excludes Provisions-related emissions).
Originally Published InKammen, D. M., Hendricks, P., Pendleton-Knoll, S., Stanley, V., & Strand, R. (2018). Patagonia's path to carbon neutrality by 2025. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Patagonia; Carbon dioxide mitigation -- Case studies; Greenhouse gas mitigation -- Case studies; Greenhouse gases -- Environmental aspects -- Case studies